Induction of Photosynthetic Carbon Fixation in Anoxia Relies on Hydrogenase Activity and Proton-Gradient Regulation-Like1-Mediated Cyclic Electron Flow in Chlamydomonas reinhardtii . Issue 2 (30th April 2015) - Godaux, Damien; Bailleul, Benjamin; Berne, Nicolas; Cardol, Pierre
Abstract : Photosynthesis and growth in anoxia depends on hydrogenase-dependent linear electron flow. Abstract: The model green microalga Chlamydomonas reinhardtii is frequently subject to periods of dark and anoxia in its natural environment. Here, by resorting to mutants defective in the maturation of the chloroplastic oxygen-sensitive hydrogenases or in Proton-Gradient Regulation-Like1 (PGRL1)-dependent cyclic electron flow around photosystem I (PSI-CEF ), we demonstrate the sequential contribution of these alternative electron flows (AEF s) in the reactivation of photosynthetic carbon fixation during a shift from dark anoxia to light. At light onset, hydrogenase activity sustains a linear electron flow from photosystem II, which is followed by a transient PSI-CEF in the wild type. By promoting ATP synthesis without net generation of photosynthetic reductants, the two AEF are critical for restoration of the capacity for carbon dioxide fixation in the light. Our data also suggest that the decrease in hydrogen evolution with time of illumination might be due to competition for reduced ferredoxins between ferredoxin-NADP + oxidoreductase and hydrogenases, rather than due to the sensitivity of hydrogenase activity to oxygen. Finally, the absence of the two alternative pathways in a double mutant pgrl1 hydrogenase maturation factor G-2 is detrimental for photosynthesis and growth and cannot be compensated by any other AEF or anoxic metabolic responses. This highlights the role of hydrogenase activity and PSI-CEF in the ecological success of microalgae in low-oxygen environments.